2023
DOI: 10.1001/jamanetworkopen.2023.37239
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Factors Associated With Postoperative Delirium in Patients Undergoing Noncardiac Surgery

Behnam Sadeghirad,
Benjamin T. Dodsworth,
Nayeli Schmutz Gelsomino
et al.

Abstract: ImportancePostoperative delirium (POD) is a common and serious complication after surgery. Various predisposing factors are associated with POD, but their magnitude and importance using an individual patient data (IPD) meta-analysis have not been assessed.ObjectiveTo identify perioperative factors associated with POD and assess their relative prognostic value among adults undergoing noncardiac surgery.Data SourcesMEDLINE, EMBASE, and CINAHL from inception to May 2020.Study SelectionStudies were included that (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Specifically, the E-value reflects the minimum strength of association that an unmeasured confounder would need to have with both the exposure and outcome, above and beyond the measured confounders, to fully explain away a specific estimated effect [ 16 ]. And reported ORs of identified risk factors for POD were compared with the E-value in present study [ 17 20 ]. Additional sensitivity analysis has also been conducted using the original, non-imputed data to detect if the results of TyG index as a binary variable are affected by imputing missing values.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the E-value reflects the minimum strength of association that an unmeasured confounder would need to have with both the exposure and outcome, above and beyond the measured confounders, to fully explain away a specific estimated effect [ 16 ]. And reported ORs of identified risk factors for POD were compared with the E-value in present study [ 17 20 ]. Additional sensitivity analysis has also been conducted using the original, non-imputed data to detect if the results of TyG index as a binary variable are affected by imputing missing values.…”
Section: Methodsmentioning
confidence: 99%
“…The etiology of delirium in these patients is typically multifactorial, and our prior research identified several risk factors for delirium in patients with cancer, including old age, absence of chemotherapy during hospitalization, hearing impairment, underweight status, current opioid use, and history of delirium and other psychiatric disorders 9 . Opioid prescriptions, in particular, have been identified in various studies as potential triggers of delirium, observed across different surgical and disease groups, including those with neurological injury, pain, infection, fever, and hypotension 4 , 10 , 11 . However, previous studies exploring the association between opioid use and delirium in patients with advanced cancer showed controversy and limited cohort size 12 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The Type and length of surgery and anesthesia are indispensable for POD prediction 18,27 . Although preoperative neuropsychological assessments, like the Mini-Mental State Examination (MMSE) and others [28][29][30] , help identify at-risk patients for early risk mitigation [31][32][33] , these evaluations…”
Section: Introductionmentioning
confidence: 99%
“…The Type and length of surgery and anesthesia are indispensable for POD prediction 18,27 . Although preoperative neuropsychological assessments, like the Mini-Mental State Examination (MMSE) and others 2830 , help identify at-risk patients for early risk mitigation 3133 , these evaluations are not yet incorporated in clinical routine despite experts’ recommendations 34 . The early identification of POD risk factors enables clinicians to proactively mitigate the occurrence of POD 35 and might affect patient’s decision before non-emergent surgery.…”
Section: Introductionmentioning
confidence: 99%